Psychological well-being of patients with arthritis: impact of psychological distress on quality of life, and patient satisfaction - Sameera Shafiq; Quratulain Muhammad; Zunaira Sajid (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Arthritis is an autoimmune disease in which individual’s immune system attack healthy cells in one’s body and giving rise to inflammation. Recently, it has been found to be manifested in individuals with stress-related diagnosis. This study investigates how psychological distress, quality of life, patient satisfaction, and the role of pharmacists affect the psychological well-being of patients who have received medical diagnoses of different forms of arthritis.METHODOLOGY: This cross-sectional study was conducted at the Department of Psychology University of Gujrat during 1st January to 30th August, 2022. A sample of 380 patients already diagnosed with arthritis by the physicians was taken by Purposive sampling technique, from various orthopedic hospitals. A demographic sheet, and Urdu versions of Depression, Anxiety, Stress Scale DASS-21, WHO QOL-BREF, Patient Satisfaction with Pharmacist Services Questionnaire and Flourishing Scale were used to assess psychological distress, quality of life, doctor patient satisfaction and psychological well-being in arthritis patients.RESULTS: The study results showed that there is a significant negative correlation between quality of life and psychological distress (r= -.11, p<0.01). Well-being and quality of life are positively correlated (r=.68, p<0.01). 57% variance in wellbeing of the patients with arthritis is explainable due to the presence of psychological distress, and perceived quality of life.CONCLUSION: The well-being of individuals diagnosed with arthritis can be strongly predicted by their levels of psychological distress and their perceived quality of life. This study delves into the implications of these findings.